2010
DOI: 10.2478/v10003-010-0014-4
|View full text |Cite
|
Sign up to set email alerts
|

Chronology Development and Climate Response Analysis of Schrenk Spruce (Picea Schrenkiana) Tree-Ring Parameters in the Urumqi River Basin, China

Abstract: Seven different tree-ring parameters (total tree-ring width, earlywood width, latewood width, maximum latewood density, minimum earlywood density, average earlywood density, and average latewood density) were obtained from Schrenk spruce in the Urumqi River Basin, China. The chronologies were analyzed individually and then compared with each other. The relationships between the different tree-ring parameters and climate data (Daxigou) are also presented. Earlywoodrelated parameters (earlywood width, minimum de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Taken together, the volcanic eruptions may have affected a large area in southwest China. Warming in the 20 th century has been observed in treering reconstructions of temperature from widespread regions of Eurasia (Jacoby et al 1996;Briffa et al 2002;Gou et al 2007;Büntgen et al 2008;Chen et al 2010). Based on instrument data and other proxies, Wang et al (2004) showed that temperature anomalies during the period 1920 -1950 are noticeably positive over China throughout the last century.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the volcanic eruptions may have affected a large area in southwest China. Warming in the 20 th century has been observed in treering reconstructions of temperature from widespread regions of Eurasia (Jacoby et al 1996;Briffa et al 2002;Gou et al 2007;Büntgen et al 2008;Chen et al 2010). Based on instrument data and other proxies, Wang et al (2004) showed that temperature anomalies during the period 1920 -1950 are noticeably positive over China throughout the last century.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, large-scale climate variations have also been successfully reconstructed (Jones et al 1998;Mann et al 1999;Briffa 2001;Esper et al 2002;Moberg et al 2005;D'Arrigo et al 2006). Trees growing close to the high altitudinal or latitudinal treeline respond to temperatures; several temperature reconstructions at high altitude have been made using tree-ring data from the Northern Hemisphere (Cook et al 2003;Esper et al 2003;Bräuning and Mantwill 2004;Büntgen et al 2008;Fan et al 2009;Wang et al 2009;Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between tree-ring indices and the climatic data were analyzed using the program DENDROCLIM2002 (Biondi and Waikul 2004). As the growth of tree may be affected not only by the climatic conditions of the current growing season but also by those of the previous growing season (Fritts 1976;Chen et al 2010), both the previous and the current growing seasons were included in the climate response analysis. The climate data used for the analysis included monthly mean temperature and total monthly precipitation over a span of 15 months (previous July to current September).…”
Section: New Chronology Developmentmentioning
confidence: 99%
“…Touchan et al, 2005;Touchan et al, 2007;Akkemik et al, 2008;Köse et al, 2011;Köse et al, 2013), in central Asia (e.g. Yuan & Li, 1999;Yuan et al, 2001;Esper et al, 2002;Yuan et al, 2003;Chen et al, 2009;Chen et al, 2010), in the southern Urals (Agafonov & Kukarskikh, 2008) and in Siberia (Rigling et al, 2001;Babushkina et al, 2015;Shah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%